Superconducting YBCO and BSCCO thin films prepared by pulsed laser deposition and post annealing / Jannah A. N. and Halim S. A. - A. N., Jannah; S. A., Halim (Universiti Teknologi MARA, Negeri Sembilan, 2012)
The YBCO and BSCCO superconducting thin films have been grown on MgO (100) by pulsed laser deposition from a sintered YBa2Cu3Oy and Bi1.6Pb0.4Sr2Ca2Cu3Oy target. Post annealing after deposition at 850OC in 30 minutes resulted in BSCCO superconducting films with zero resistance at 52 K. YBCO film annealed for 2 hours is non-superconducting but it is improved by increasing the time to 4 hours and 5 hours at 920OC . X-Ray diffraction pattern shows a predominance of 001 peaks for BSCCO film and no improvement of crystallinity after annealed for YBCO film.